Digital Social Interaction and Identity Construction among Generation Z in Urban Indonesia - Sahal Hanafi; Fadli Agus Triansyah; Rosyid Ridlo Al-Hakim; Rafidha Nur Alifah; Abdul Kholik (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates how digital social interaction shapes identity construction among Generation Z in urban Indonesia through an empirical qualitative multi-site design integrating interviews, digital ethnography, and reflective media diaries. Findings show that linguistic stylization and multimodal self-presentation operate as core infrastructures of symbolic identity work, while relational feedback loops within peer networks stabilize belonging through validation, humor, and contextual negotiation. Moral and aspirational framings further anchor digital expression in ethical reasoning, cultural continuity, and future-oriented self-projection linked to urban opportunity structures. Cross-case analysis demonstrates that identity emerges as a relational, reflexive, and platform-mediated process in which language, symbolism, and social recognition co-produce durable self-narratives. The study contributes a multi-level framework connecting discursive micro-practices with moral and aspirational logics, advancing theoretical understanding of youth digital identity and offering methodological templates for analyzing mediated subjectivity in rapidly transforming urban societies, highlighting how everyday interaction accumulates into socially regulated identity trajectories that integrate creativity, community, and ethical self-formation within contemporary platform ecologies, providing empirically grounded insight for interdisciplinary scholarship on digital youth.